Impacto del Jamboard en exposiciones virtuales - Pezo Romero, Jesús Antonio (2023)
The purpose of the study was to be able to evaluate the use of the Jamboard virtual whiteboard in virtual exhibitions, with secondary school students, the work was carried out through a pre-experimental design applying a pre-test and a post-test, with a sample of thirty-five third-year high school students at the Virgen de Loreto Educational Institution, the techniques and instruments used in the research were the survey with a questionnaire and direct observation with a data collection sheet, the most relevant results were: in the evaluation of virtual exhibitions without the use of Jamboard, 25.1% of students did a good job and but when applying Jamboard, this percentage rose to 69.7%, so there is an indicator that there was indeed an improvement in the execution of virtual exhibitions